Hom-Lie algebroids - Laurent-Gengoux, Camille (2013)
We define hom-Lie algebroids, a definition that may seem cumbersome at first, but which is justified, first, by a one-to-one correspondence with hom-Gerstenhaber algebras, a notion that we also introduce, and several examples, including hom-Poisson structures.